EFEKTIVITAS MODEL PEMBELAJARAN LEARNING CYCLE 5E MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VII SMPN 2 PONTIANAK - Elisa, Iit; Aminuyati, Aminuyati; Achmadi, Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract The purpose of this research was to found out the learning model learning cycle 5e with conventional learning model application. The method in this research was quasi experiment with planning non-equivalent control group design. The tools of data collection were multiple choices test and observation sheet. The result of hypothesis that used one sample t test with α = 5% was Zvalue = 9.884 (Z value > Z table), was in rejected area Ho. This result showed that there was significance difference between students’ learning outcome that applied learning model learning cycle 5e and the students that applied conventional model. In experiment class, after conducted the treatment with application of learning model learning cycle 5e there was an increasing mean, from pre-test mean 54.58 to post-test mean 86.38. Experiment class also had improvement in mastery percentage score from 83.3% pre-test mastery percentage to 100% post-test mastery percentage. It could be concluded that learning model learning cycle 5e in social interaction material on Class VII of SMP Negeri 2 Pontianak showed the effective criteria through students’ learning outcome, in mastery percentagedifference 91.67% and effect size with score 0.81. Keywords: Effectiveness, Learning Cycle 5E Models